2016
DOI: 10.1016/j.gca.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Chromium uptake and adsorption in marine phytoplankton – Implications for the marine chromium cycle

Abstract: Using the radioisotope 51 Cr, we investigated the controls of cellular Cr accumulation in an array of marine phytoplankton grown in environmentally relevant Cr concentrations (1-10 nM). Given the affinity of Cr(III) for amorphous Fe-hydroxide mineral surfaces, and the formation of these mineral phases on the outside of phytoplankton cells, extracellular Cr was monitored in a model diatom species (Thalassiosira weissflogii) as extracellular Fe concentrations varied. Extracellular Cr in T. weissflogii increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 100 publications
0
50
1
Order By: Relevance
“…Semeniuk et al () presented a similar calculation. Our calculation differs in two main ways: (1) Our [Cr] deficits are calculated comparing water above the winter mixed layer and the immediately underlying waters rather than comparing the mixed layer to waters at ≥500 m, and therefore our calculated Cr deficit is smaller; and (2) we use phytoplankton Cr data from the open North Pacific (Martin & Knauer, ) and exported particles in the open North Atlantic (Connelly et al, ), rather than data from North Atlantic marginal seas (Dauby et al, ), which show a much higher Cr:C (~20 μmol Cr mol/C) and may not be representative of the open ocean.…”
Section: Resultsmentioning
confidence: 75%
“…Semeniuk et al () presented a similar calculation. Our calculation differs in two main ways: (1) Our [Cr] deficits are calculated comparing water above the winter mixed layer and the immediately underlying waters rather than comparing the mixed layer to waters at ≥500 m, and therefore our calculated Cr deficit is smaller; and (2) we use phytoplankton Cr data from the open North Pacific (Martin & Knauer, ) and exported particles in the open North Atlantic (Connelly et al, ), rather than data from North Atlantic marginal seas (Dauby et al, ), which show a much higher Cr:C (~20 μmol Cr mol/C) and may not be representative of the open ocean.…”
Section: Resultsmentioning
confidence: 75%
“…The study of Farkaš et al (2018) Wang et al (2016) could be envisaged as to result from variable Cr uptake mechanisms. These authors propose that in regions with high dissolved organic matter, foraminifera could preferentially uptake Cr(III) associated with dissolved organic phases and/or organic matter, as observed for some phytoplankton (Semeniuk et al, 2016). In regions where dissolved organic concentration is low, foraminifera may switch to the reductive Cr(VI) uptake mechanism, as proposed for coral growth (Pereira et al, 2015).…”
Section: Shells -Chromium Isotope Compositions and Chromium Concentramentioning
confidence: 90%
“…Such high D Cr values observed in biogenic carbonates produced by different marine organisms point to a strong biological control over the incorporation of Cr from seawater into CaCO 3 skeletons, where it could be incorporated either as Cr(III) and/or Cr(VI) depending on species-specific redox cycling of Cr (cf. Wang et al, 2016;Semeniuk et al, 2016) and/or, as recently suggested, directly assimilated as 4916 R. Frei et al: A systematic look at chromium isotopes in modern shells organic ligand-bound Cr during biological uptake (Saad et al, 2017). It is too premature to compare the biogenic distribution coefficients with abiogenic values, simply because there is a lack of suitable modern seawater-carbonate pairs from which such values could be calculated.…”
Section: Individual Shells -Chromium Distribution Coefficients (D Cr mentioning
confidence: 99%
See 2 more Smart Citations